URDU-A RESEARCH REVIEW OF MAULANA DIN MUHAMMAD WAFAI'S WORK ON RELIGIOUS AND LITERARY BIOGRAPHY - Asfan Khatoon Khushk; Bashir Ahmed Rind (دی اسکالر)
Maulana Din Mohammad Wafai was an eminent religious scholar, freedom fighter, journalist, columnist, historian, and best biographer. There are many important aspects of his life, each of which is required to write permanent articles. This article presents an overview of his biographical work.  His services are so extensive in the biography that the personality of the biographer is well known. One of the topics of his biography is the biography of the companions. The biography of saints and the scholars have been his subject. Various personalities on the subject of biography were constantly written in the form of editorials or impressions during his journalistic career, as well as his excellent book on the subject of "Tazkara Mashkir Sindh". Hence, all of his biographical services are presented in this article along with all types of biographical reviews.